CIAT/PABRA Ukama Ustawi (UU) annual nutrition deliverables: Summary report for 2023 - Munthali, Justice; Chideya, Yohane; Rubyogo, Jean Claude (2023)
Under WP 1, CIAT/PABRA promotes beans as means of contributing to the wellness of the food system, including climate adaptation, as well as the business environment. The nutrition component implemented its planned activities through partnerships with NARES and private sector players (SMEs). Eight NARES partners were engaged (three in SABRN and 5 in ECABREN) and eleven private sector players were engaged (seven in SABRN and four in ECABREN). As a result, more than 731 field demonstrations using food basket approach were mounted (100 in Zambia, 17 in Uganda, 9 in Zimbabwe and 605 in Malawi). High iron bean seeds and bean-based food products were distributed to more than 3,457 farmers. More than 1,503 (531M; 972F) farmers were trained on and benefited from food basket approach and gender sensitive interventions. Two policies reviews were conducted in Uganda and Kenya. Four dialogue meetings were held in Kenya Uganda and Zimbabwe to influence policies. Five stakeholders have been engaged to influence policies in Uganda, Kenya, and Zimbabwe and four policies were influenced in Kenya, Uganda, and Zimbabwe. Eleven processors (SMEs) were identified and received UU grants to support strengthening and efficiency of their businesses. Out of the eleven, 6 already purchased various small processing machines, one processor’s machine is still under fabrication, one processor is yet to receive funds due to funds transfer errors and three processors are yet to provide status update. More than 10 SMEs in Zimbabwe were trained on value addition and commercialization of bean products to fight malnutrition in the country. Processors in Malawi, Zambia and Uganda were coached and mentored on business topics. Nineteen SMEs were linked to 19 stakeholders for business advisory services. More than 29 recipes were promoted in Malawi, Zimbabwe, Kenya, Uganda and Zambia. The recipes were adopted from existing recipe booklets. However, 1 recipe booklet was developed using UU project funds in Kenya. The interventions and activities implemented to promote bean-based nutritious products were generally good. Issues of gender and climate adaptability and mitigation were mainstreamed, and private sector players were engaged.